Website Gallery Development Using Tailwind CSS Framework - Fadli Rifandi; Tri Viqi Adriansyah; Rina Kurniawati (Jurnal E-Komtek, 2022)
This research designs and builds a special website for photography galleries, where this application is made to help and make it easier for photographers to store and exhibit photography widely via online media. So far, the storage media for exhibiting photographers' results is still conventional, for example exhibitions of certain photographers' artworks or special events. This makes it difficult for art enthusiasts or novice photographers to see or display their photography results. The website design uses the waterfall method and uses HTML, CSS programming language tools with the TailwindCSS framework, PHP, and MySQL as the database.